Implementation of the Balanced Nutrition Pocket- Flipbook to Improve Elementary School Children’s Nutritional Knowledge - Mustikaningrum, Ardian Candra; Infitharina, Erna; Nafilah, Nafilah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
This study aimed to examine the effect of E-Bukuku, a flipbook-based digital pocketbook on balanced nutrition, in improving nutrition knowledge among elementary school children. The study employed a pre-experimental one-group pretest–posttest design conducted at Purin Muhammadiyah Kendal Elementary School. A total of 162 students aged 7–9 years were selected using purposive sampling. The intervention was delivered through a structured nutrition education session. Students were guided by the researcher or classroom teacher to interactively explore the E-Bukuku flipbook through page navigation, illustrations, question-and-answer sessions, brief discussions, and practical examples to reinforce balanced nutrition messages. After the session, students were given time to independently review the material before completing the posttest using the same questionnaire as the pretest. Nutrition knowledge was measured using a structured questionnaire integrated with the E-Bukuku content. Data were analyzed using the Wilcoxon signed-rank test, as the paired pretest and posttest data did not meet the normality assumption. The results showed a statistically significant improvement in nutrition knowledge following the intervention, with mean scores increasing from 55.30 ± 8.12 at pretest to 82.75 ± 6.45 at posttest (p < 0.001). In conclusion, the use of E-Bukuku significantly improved balanced nutrition knowledge among elementary school children. E-Bukuku can be considered an innovative digital-based nutrition education medium. This study provides preliminary evidence supporting the effectiveness of flipbook-based digital nutrition education and offers insights for future large-scale interventions.